Pengaruh Model Pembelajaran Quantum Reading Terhadap Kemampuan Membaca Dan Minat Baca Siswa Mata Pelajaran IPS Kelas Ⅶ Di SMPN 1 Pagu Kabupaten Kediri - Ipna Nurani; Hendra Pratama (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
This research is motivated by the lack of students' reading ability and interest in reading at SMPN 1 Pagu and they prefer fun activities because they think that reading is boring unlike when reading novels, comics and other picture books. So in this case it requires special attention from teachers and parents to provide extra education for children so that they are interested in reading and improve their reading comprehension skills, both at home and especially at school. The formulation of the problem is 1) What is the influence of the Quantum Reading Learning Model on Students' Reading Comprehension Ability in Class Ⅶ Social Sciences Subjects at SMPN 1 Pagu? ; 2) What is the influence of the Quantum Reading Learning Model on Students' Reading Interest in Social Sciences Subjects in Class Ⅶ at SMPN 1 Pagu? . The research objectives in this thesis are 1) To determine the effect of the Quantum Reading learning model on students' reading comprehension abilities in class VII social studies at SMPN 1 Pagu; 2) To determine the effect of the Quantum Reading learning model on students' reading interest in social studies subjects at SMPN 1 Pagu, Kediri Regency in 2023/2024. This research uses a quantitative approach. Quasi experimental type of quantitative research. The population in this study were all class VII students at SMPN 1 Pagu, Kediri Regency. The samples in this research were class VII B students consisting of 36 students and class VII C consisting of 36 students. Data collection techniques use questionnaires and tests. The data analysis technique used is the paired sample T test (Paired Sample T Test). The results of the research show that 1) the Quantum Reading learning model has an influence on the Reading (Comprehension) of Class VII students at SMPN 1 Pagu, Kediri Regency 2023/2024, as evidenced by the obtained significance value (2-tailed) 0.000 < 0.05, so H0 is rejected and Ha is accepted. 2) the Quantum Reading learning model influences the reading interest of Class VII students at SMPN 1 Pagu, Tulungahung Regency 2023/2024, as evidenced by the acquisition of students' reading interest with a significance (2-tailed) of 0.000 < 0.05, so H0 is rejected and Ha is accepted.